PENGARUH UMUR PINDAH TANAM DAN JUMLAH BIBIT PER LUBANG TANAM TERHADAP PERTUMBUHAN DAN PRODUKSI PADI (Oryza sativa L.) - Muhammad Jalil; Diswandi Nurba; Irvan Subandar; Muhammad Amin; Teuku Raja Malikon (Jurnal Agrotek Lestari, 2018)
The aims the research were to know the influence of age and number of planting seed/hole towards the growth and yield of rice plants, as well as real whether the interaction of both of these factors. The research was arranged by Randomized Block Design (RBD) factorial with 3 replicates. Treatment of replanting are : 10, 15, 20 and 25 after germination. The number of seeds are: 1, 2, and 3 seeds/hole. The research was conducted in Gampong Blang Baro sub-district of Kuala District Nagan Raya from January 10-May 08 2014. The results showed the replanting gave significant effect of the planlet number at 15 and 45 day after planting (DAP), significant of long panicles. Not significant on high of plant at 15, 30and 45 DAP, number of plantlets per clump at 30 DAP, flowering age and the number of plantlets per clump, high productive plants when harvesting, the number of panicle, pithy grain percentage, the percentage of empty grain, weights 100 grain, dried grain per plot and production yield per acre. The amount of seed gave significant effect against number of planlets at 15 DAP, not significant against plant at 15, 30 and 45 DAP, number of plantlets per clump age 30 and 45 DAP, flowering age and the number of plantlets per clump, high productive plants when harvesting, the number of panicle productive, panicles, pithy and hollow grain percentage, weight of dried grain per plot and production per acre. There is a very real interaction between age and total seedling planting move per planting hole against number of planlets at 15 DAP 100 grain weight and grain. Keywords : replanting, count of seed, growth and production of rice plant